Village Fund for Renewable Energy Development: A Case Study of Rural Area in Indonesia - Marianti, Maria Merry; Permatasari, Paulina; Manurung, Elvy Maria; Wardana, Irwanda Wisnu; Alim, Tri Emil; Wahyuputri, Firli Wulansari (International Journal of Energy Economics and Policy, 2023)
Energy is a fundamental element for development in all countries. However, the problem is that not all people have access to energy, especially in Indonesia where 42% of the population lives in rural areas. The Indonesian government has created a Village Funds program to improve rural and energy development. This study aims to uncover the effectiveness of using the Village Fund, especially for affordable and clean energy, to support achieving Sustainable Development Goal number 7. The method used in this research is a case study method using document study and several interviews with the member of Fiscal Ministry of Indonesia. The result shows that after mapping all Village Funds activities during 2018-2020, Kalimantan and Sulawesi become the most extensive realization of the use of Village Funds to alternative and renewable energy activities. To achieve SDGs number 7, the allocation of Village Funds for renewable energy development still needs to be increased, especially in the island of Java. The role of government in making Village Funds policy is still required. Village development should not only focus on infrastructure, but the affordability of village communities to develop clean and renewable energy is also important.